Management Solutions for the Restructuring of Laboratories Associated to the Sentinel Services for Syphilis and Other STIs - Coutinho, Karilany Dantas; Valentim, Ricardo A. de M.; Vieira, Geir Veras; Sidrim, Maíra; Evangelista, Pedro Henrique Germano; Oliveira, Laís Pereira de (Frontiers in Public Health, 2022)
This article aims to develop management solutions to accompany the processes of acquiring and distributing equipment and/or materials needed for the restructuring of associated laboratories to the sentinel services (Sentinel Laboratories) for syphilis and other sexually transmitted infection in the scope of the “Syphilis No!” Project. To this end, we have taken steps to create an overview of the restructuring project for the sentinel laboratories, define the stages of project execution, monitor the implementation of the project, and elaborate a standard operating procedure for the delivery of equipment and/or materials to the sentinel laboratories. Among the results, we highlight: the detailed workflow for the process of public procurement through direct purchases or bidding; the workflow for storage of the equipment and materials; the standard operating procedures (SOP) for contact with the laboratories; and the SOP for delivery of items acquired for the sentinel laboratories.